Hemodialysis Duration and Symptom Burden in Patients with Chronic Kidney Disease - Putri, Ni Kadek Winda Handayani; Antari, Gusti Ayu Ary; Manangkot, Meril Valentine; Prapti, Ni Ketut Guru (Jendela Nursing Journal (JNJ), 2025)
Background: hemodialysis is the most common renal replacement therapy for patients with chronic kidney failure. While hemodialysis therapy can prolong the life expectancy of patients, this therapy can also cause side effects that become a symptom burden for patients. Symptom burden is the combination of physical and psychological symptoms felt by patient. The severity of symptom burden can be influenced by various factors, one of them is the length of the patient undergoing hemodialysis. Purpose: the purpose of this study was to determine the relationship between the length of hemodialysis and symptom burden in patients with chronic kidney failure undergoing hemodialysis at Buleleng Regional General Hospital. Methods: this study was a descriptive correlational study with a cross-sectional approach and involved 70 respondents with chronic kidney failure obtained through purposive sampling technique. The instrument in this research used the Chronic Kidney Disease Symptoms Burden Index (CKD-SBI) and data analysis used the Chi Square test. Results: most respondents had undergone hemodialysis for ≥1 year (72.9%). Patients experienced an average of 14 symptoms with a mean symptom burden score of 21.07. The majority had mild symptom burden (84.3%). A significant relationship was found between the length of hemodialysis and symptom burden (p = 0.000) Conclusion: the duration of hemodialysis is significantly associated with symptom burden in chronic kidney failure patients. These findings highlight the importance of monitoring symptom burden, particularly among long-term hemodialysis patients.